Rationalizing Taiwan’s climate action based on oceans: ineffective governance, aspiring international participation, unrealized universal values, and a new window of blue carbon ecosystem measure - Tseng, Hui-Yi Katherine; Kao, Shih-Ming; Tseng, Huan-Sheng (Frontiers in Marine Science, 2023)
Characterized with unique practices of self-imposed voluntary commitment, the formulation of Taiwan's climate action has been informed with the logic of appropriateness, which is norm-guided without regard to consequences. However, ineffective governance exhibited in the gap between governance incapability and overcommitted contribution, aspiring international participation, realization of universal values hindered by a developmentalism mindset, altogether reifies that Taiwan's climate action has turned out as a self-deceiving prophecy. It requires due consideration of socially-constructed roles and matching obligations (the appropriateness concern) on one hand, and promulgation of actions made upon rational choice along with well-defined interests (calculation of consequences) on the other hand, to deliver Taiwan's voluntary commitments, while living up the name and substance of an earth citizen. Taiwan's effort at developing the blue carbon ecosystem (BCE) measure may open a new window of opportunity, whereby a paradigmatic shift in transforming the appropriateness logic to one of appropriateness-consequences compound, is discernible. The key lies in: integrating the developmentalist drive for growth and the rising environmentalist demand, while engaging, substantially and extensively, members of those affected communities, with more accessible and sustainable financing mechanisms.